Auris keyboard: ferramenta de auxílio ao treinamento de percepção musical para pessoas surdas - Sá, Caio Vinícius Pereira de (2019)
The present research deals with the process of inclusion of deaf individuals to the formal teaching of music, through the translation of sound information into tactile vibration. From the understanding of the tools and methodologies already used to support the teaching of music for deaf people, it was possible to develop a new tool containing some of the main successful characteristics in previous studies. A qualitative research was then carried out, based on experiments carried out with groups of deaf individuals and listeners, who used the built prototype, and generated information to support an analysis of the capacity of the tactile perception of rhythmic and melodic elements. The use of the tool was evaluated as positive for the cases addressed, suggesting that the translation of sound to tactile vibrations is possible and can be used for activities related to the formal teaching of music